Anti-inflammatory and nephroprotective activity of Juglans mollis against renal ischemia–reperfusion damage in a Wistar rat model - Perez-Meseguer, Jonathan (BMC Complement Altern Med, 2019)
BACKGROUND: Oxidative stress and the inflammatory process are involved in ischemia–reperfusion (I/R) injury. Juglans mollis has been reported as having antioxidant activity, which could attenuate the damage caused by I/R. We evaluated whether a methanolic extract of Juglans mollis (JM) exhibits nephroprotective activity in a Wistar rat model of I/R injury. METHODS: Four groups of six rats were used: Sham, I/R, JM, and JM + I/R. Two groups were dosed with JM (300 mg/kg) for 7 days before I/R. I/R injury was induced by clamping the renal hilums for 45 min and then reperfusing the kidneys for 15 h. Blood samples were taken to evaluate the levels of alanine aminotransferase (ALT), blood urea nitrogen, creatinine, superoxide dismutase (SOD), malondialdehyde (MDA), interleukin 1β (IL-1β), IL-6, and tumor necrosis factor α (TNF-α). RESULTS: The levels of creatinine, ALT, MDA, IL-1β, IL-6, and TNF-α were lower in JM + I/R than in I/R rats, whereas SOD level only was higher in JM + I/R than in Sham rats. No biochemical or histological damage was observed in JM rats compared with Sham rats; however, less histological damage was observed in JM + I/R rats compared with I/R rats. CONCLUSIONS: To our knowledge, this is the first report of nephroprotective activity of J. mollis against damage induced by I/R. This activity may be related to decreased levels of proinflammatory cytokines (IL-1β, IL-6, and TNF-α) and modulation of oxidative stress markers (SOD and MDA) observed in the present study.